Hazard mitigation and preparedness an introductory text for emergency management and planning professionals - Schwab, Anna K.; Sandler, Dylan; Brower, David J. (CRC Press, Taylor & Francis Group, 2017)
This book introduces the concept of hazards as part of the earth's natural systems, in contrast to "disasters," which occur at the intersection of the built and natural environments. The book defines key concepts including mitigation, preparedness, resilience, and vulnerability, and explains the role of the emergency manager in putting these principles into practice.